Microscopic Evolution of Pore Characteristics and Particle Orientation of Granite Residual Soil in One-Dimensional Compression - Gang Wang; Xianwei Zhang; Xinyu Liu; Yiqing Xu; Jianfeng Lu (Geofluids)
This study investigates the microstructural changes of granite residual soil (GRS) upon compression, the aim being to understand further the deformation mechanism from a microscopic perspective and establish the relationship between the mechanical behavior and microstructural characteristics of GRS. By means of (i) experimental compression tests with different loadings and (ii) scanning electron microscopy (SEM), the structural evolution of GRS during compression tests is investigated systematically from both macroscopic and microscopic perspectives. Microstructural characteristics including particle morphology, pore size distribution, and particle preferred orientation are investigated specifically through SEM quantification methods. With an obvious turning point, the e–log σv′ curve for natural GRS approaches the intrinsic compression line gradually when the vertical pressure exceeds the preconsolidation pressure, which indicates the significant influence of cementation bonding on the mechanical behavior of intact GRS. At the microscopic scale, the deformation of natural GRS is attributed to the compression and transformation of large pores, while the deformation of remolded GRS is also related to the transformation from mesopores to small pores. Upon compression loading, particles show higher preferred direction angle perpendicular to vertical loading, thereby facilitating the preferred orientation. With increasing vertical loading, the microfabric can no longer sustain the initial alignment pattern and tends to be rearranged and reoriented into a more stable and stronger structure. This study offers guidance for the deformation analysis of subgrade related to GRS.